Halal dalam Citra, Haram dalam Praktik: Kritik terhadap Kekerasan di Lingkungan Pesantren - Lailatur Rohmah; Hidayatul Maghfiroh (Prodi Ahwal Asy Syahsiyah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2024)
Islamic boarding schools (pesantren) in Indonesia are widely regarded as important religious institutions that contribute to the development of moral values, discipline, and spiritual character in society. These institutions are commonly associated with ethical education, modest living, obedience, and religious devotion. Despite this positive public perception, incidents of violence within pesantren environments have become an increasing social concern. Cases involving physical, verbal, and psychological violence have been reported among students, senior members, administrators, and occasionally teachers. This research seeks to analyze the gap between the ideal image of pesantren as moral and religious institutions and the reality of violent practices that continue to occur within them. The study employs a qualitative method using a phenomenological approach to understand the experiences and social realities faced by students in pesantren life. Data were gathered through interviews, observations, and documentation. The results indicate that violent practices are frequently justified as part of disciplinary processes and character formation. The persistence of violence is influenced by a strong culture of seniority, unequal social relations, and institutional efforts to preserve the reputation of pesantren in the public sphere. These conditions also contribute to the emergence of a culture of silence among victims. Therefore, this study argues that violence in pesantren should be understood not only as an individual act, but also as a structural and cultural problem within Islamic educational institutions.